2020
DOI: 10.1016/j.jamcollsurg.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis Shutdown Correlation with Thromboembolic Events in Severe COVID-19 Infection

Abstract: BACKGROUND: COVID-19 predisposes patients to a prothrombotic state with demonstrated microvascular involvement. The degree of hypercoagulability appears to correlate with outcomes; however, optimal criteria to assess for the highest-risk patients for thrombotic events remain unclear; we hypothesized that deranged thromboelastography measurements of coagulation would correlate with thromboembolic events. STUDY DESIGN: Patients admitted to an ICU with COVID-19 diagnoses who had thromboelastography analyses perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
464
4
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(522 citation statements)
references
References 40 publications
(42 reference statements)
38
464
4
16
Order By: Relevance
“…The number of patients varied from 11 to 328, with mean age of 64.3 years (from 51.7 to 80.5 years). Eleven studies 18,19,21,24,25,28,30,[32][33][34]36 specifically enrolled patients admitted to ICU. A total of 66.8% of patients were males (range: 45.7-90.9%) and the mean BMI was 28.2 kg/m 2 (range: 23.6-31.3 kg/m 2 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of patients varied from 11 to 328, with mean age of 64.3 years (from 51.7 to 80.5 years). Eleven studies 18,19,21,24,25,28,30,[32][33][34]36 specifically enrolled patients admitted to ICU. A total of 66.8% of patients were males (range: 45.7-90.9%) and the mean BMI was 28.2 kg/m 2 (range: 23.6-31.3 kg/m 2 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The thrombotic complications observed in COVID-19 include several unusual features that differ from disseminated intravascular coagulation (DIC), e.g. elevated fibrinogen and fibrin D-dimer, hyperreactive platelets, and formation of microthrombi in multiple organs, but without the consumption of coagulation factors that typically accompany other severe inflammatory conditions such as sepsis [6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of microthrombi formation in AKI has been found in postmortem ndings, where there is erythrocyte stagnation with clot formation in the glomerular and peri-tubular capillaries in COVID-19 patients [6]. Moreover, one study demonstrated that elevated D-Dimer level and complete failure of lysis at 30 minutes on a thromboelastogram are predictive of signi cant increase in the incidence of thromboembolism and a need for haemodialysis in critically ill COVID-19 patients [21]. In our report, the development of AKI was associated with raised admission D-dimer levels and these abnormalities persisted in patients with AKI even after a week of ICU admission.…”
Section: Discussionmentioning
confidence: 98%